European LeukemiaNet 2020 recommendations for treating chronic myeloid leukemia - Hochhaus, A; Baccarani, M; Silver, R T; Schiffer, C; Apperley, J F; Cervantes, F; Clark, R E; Cortes, J E; Deininger, M W; Guilhot, F; Hjorth-Hansen, H; Hughes, T P; et al. (Leukemia, 2020)
The therapeutic landscape of chronic myeloid leukemia (CML) has profoundly changed over the past 7 years. Most patients with chronic phase (CP) now have a normal life expectancy. Another goal is achieving a stable deep molecular response (DMR) and discontinuing medication for treatment-free remission (TFR). The European LeukemiaNet convened an expert panel to critically evaluate and update the evidence to achieve these goals since its previous recommendations. First-line treatment is a tyrosine kinase inhibitor (TKI; imatinib brand or generic, dasatinib, nilotinib, and bosutinib are available first-line). Generic imatinib is the cost-effective initial treatment in CP. Various contraindications and side-effects of all TKIs should be considered. Patient risk status at diagnosis should be assessed with the new EUTOS long-term survival (ELTS)-score. Monitoring of response should be done by quantitative polymerase chain reaction whenever possible. A change of treatment is recommended when intolerance cannot be ameliorated or when molecular milestones are not reached. Greater than 10% BCR-ABL1 at 3 months indicates treatment failure when confirmed. Allogeneic transplantation continues to be a therapeutic option particularly for advanced phase CML. TKI treatment should be withheld during pregnancy. Treatment discontinuation may be considered in patients with durable DMR with the goal of achieving TFR.
Keywords: Dasatinib; konsensuální konference jako téma; Quinolines; pyrimidiny; inhibitory proteinkinas; naděje dožití; monitorování fyziologických funkcí; Quality of Life; Monitoring, Physiologic; Aniline Compounds; bcr-abl fúzní proteiny; chinoliny; kvalita života; lidé; Survival Analysis; chronická myeloidní leukemie; Antineoplastic Agents; protinádorové látky; Clinical Decision-Making; dasatinib; klinické rozhodování; aniliny; Consensus Development Conferences as Topic; imatinib mesylát; Protein Kinase Inhibitors; nitrily; Nitriles; Disease Management; analýza přežití; exprese genu; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; Life Expectancy; Imatinib Mesylate; Gene Expression; management nemoci; Pyrimidines; Humans